Wireless mobile communication and healthcare Second International ICST Conference, MobiHealth 2010, Ayia Napa, Cyprus, October 18-20, 2010, revised selected papers - Lin, James C.; Nikita, Konstantina S. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering1, 2011)
This book contains a selection of thoroughly refereed and revised papers from the Second International ICST Conference on Wireless and Mobile Communication in Healthcare, MobiHealth 2010, held in Barcelona, Spain, in May 2010. The 33 papers in this volume describe various applications of information and communication technologies in healthcare and medicine and cover a wide range of topics such as intelligent public health monitoring services, mobilehealth technologies, signal processing techniques for monitoring services, wearable biomedical devices, ambient assistive technologies, emergency and disaster applications, and integrated systems for chronic monitoring and management.